SAT0413 Sympathetic Skin Response in Diabetic Patients with Soft Tissue Rheumatism of the Hand. (23rd January 2014) - Soliman, E.; Al-Moghazy, H.; Mohasseb, D.; El-tantawi, G.; Naeem, S.
Abstract : Background: Musculoskeletal complications of the hand may be very debilitating for the diabetic patient. The most commonly recognized complications are trigger finger, tenosynovitis, Dupuytren's contrcture, carpal tunnel syndrome (CTS), and limited joint mobility (LJM). Increased glycosylation has been suggested as the pathogenesis of soft tissue lesions of the hand in diabetic patients. Glycosylation of basement membrane explains the associated microangiopathy and impaired micro-circulation. Diabetic autonomic neuropathy of the sympathetic system has been implicated in the pathogenesis of different diabetic complications as a consequence of impaired tissue perfusion. This may raise the possibility of an association between diabetic hand soft tissue lesions and diabetic autonomic neuropathy. Objectives: To investigate the relationship between sympathetic dysfunction and soft tissue rheumatism of the hand in diabetic patients. Methods: the study included 2 groups:group 1 included 20 diabetic patients with at least one hand soft tissue lesion and group 2 were 20 diabetic patients without any hand pathology. All patients were thoroughly evaluated clinically and were assessed for the presence of diabetic sympathetic neuropathy using tilt table test before proceeding to the electrophysiological measurements. Electrodiagnostic techniques included sensory conduction studies of median, ulnar, and superficial radial nerves, and motor conduction studies of median and ulnar nerves and testing sympathetic skin response (SSR) of the hand. In addition, the axillary F central loop latencies for the median and ulnar nerves were determined. Results: Six patients in group 1 had CTS, 5 had trigger fingers, 2 had tenosynovitis, 2 had LJM, and one had Dupuytren's contracture. In addition, 4 patients had combined CTS and LJM. Abnormal SSR was detected in 10 patients in group 1 and in 10 patients in group 2. There was no statistically significant difference between group 1 and 2 regarding the frequency of SSR abnormalities. There was a statistically significant relationship between the presence of CTS in group1 patients and abnormal SSR results. There was a statistically significant relationship between positive tilt table test results in group 1 patients and abnormal SSR in the same group. The presence of SSR abnormalities was related to prolonged duration of diabetes in group1 patients. Conclusions: Diabetic patients with CTS tend to have prolonged SSR of the hand. Otherwise, the presence of soft tissue lesions of the hand is not related to autonomic sympathetic neuropthy in patients with diabetes. Disclosure of Interest: None Declared